Kulturell kritik och komplexitet - Sten Dahlstedt (Lychnos, 2009)
This is an article on the reception of the work of Theodor W. Adorno in Sweden. It stretches from the late 1920’s, when he came to notice as a radical critic of music, to the early 1980’s, when the Swedish translation of his and Horkheimer’s Dialektik der Aufklärung gained him a firm place in intellectual life. Before then he was mostly known as a left-wing intellectual with extreme opinions on jazz and popular music. Eventually, he also became acknowledged as a critic of Kierkegaard, an aesthetician and a critic of modern culture.